XIèmes Journées, Les Sables d'Olonne 2010
DOI: 10.5150/jngcgc.2010.095-l
|View full text |Cite
|
Sign up to set email alerts
|

Dredged marine sand as constructive material

Abstract: Abstract:Dredging works are usually required to maintenance activities in many ports all over the world and represents a huge volume of disposal material. The use of dredged aggregates can be considered in several applications as erosive process control, coastal stabilization, beach replenishment, production of construction materials (clay, bricks, aggregates) or construction works (foundation fill, dikes, etc.). Researches revealed the feasibility of dredged marine sand (DMS) in the construction of base and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Faster hydration generates a greater amount of hydration products, such as calcium silicate hydrate (C-S-H), which blocks the pores in the resulting concrete and thus enhances the early strength development [2,16].…”
Section: Effect Of Seawater and Sea Sandmentioning
confidence: 99%
See 1 more Smart Citation
“…Faster hydration generates a greater amount of hydration products, such as calcium silicate hydrate (C-S-H), which blocks the pores in the resulting concrete and thus enhances the early strength development [2,16].…”
Section: Effect Of Seawater and Sea Sandmentioning
confidence: 99%
“…Relevant studies have demonstrated that the utilization of sea-sand [2,10] and seawater [11][12][13] in concrete increases early-age compressive strength, lowers long-term compressive strength [14,15], makes the concrete less workable [16], and increases drying shrinkage [17,18] compared to fresh water and river sand counterparts due to the salt and sea-shell contents present in them.…”
Section: Introductionmentioning
confidence: 99%
“…As for the sustainable marine sediments management, this imposes a storage on ground of the non-or contaminated sediments and requires the development of processes of treatment and of reuse. The first paper, written by Limeira, Agulló, and Exteberria (2012), discusses a very important topic, which is the problem of dredged sediments. This work deals with the study of dredged marine sand from the Port of Sant Carles de la Ràpita (Tarragona, Spain) as construction material.…”
Section: Editorialmentioning
confidence: 99%
“…The third project served to enhance sediment into a landscaped eco-model; this project consisted of the implementation of landscaping eco-models made of sediments from 5 to 7 m high and covered with 0.25 m of topsoil to ensure the stability of the structure. In addition, dredged sediment has been used in some countries in major infrastructure projects, such us Palm Island in Dubai, Rotterdam harbor, the National Theatre in London and the artificial island of Chek Lap Kok where the Hong Kong airport is located [72,92,93]. The success of these projects confirms and verifies the economic and technical validity of reusing dredged sediment in civil engineering [94].…”
Section: Introductionmentioning
confidence: 97%